Pandangan Mori Ogai terhadap Euthanasia (Anrakushi) dalam Takase Bune - Unsriana, Linda (Humaniora, 2010)
Mori Ogai is a welknown Japanese author in the modern Japanese literature, that is literatures that reflect a modern society living. This modern society tries to disclose social status and raise freedom and righyt equality as the basic of modern life. One of his novels, Takase Bune clarifies Mori Ogai views on Euthanasia (Anrakushi). Article presents the views of a prominent writer as well as medical practitioner on the Japanese Army on Euthanasia practice.